2021
DOI: 10.1186/s40634-021-00343-0
|View full text |Cite
|
Sign up to set email alerts
|

A false-pouch closure technique with an intact superior peroneal retinaculum for recurrent dislocation of the peroneal tendon

Abstract: Purpose To evaluate the usefulness of the false-pouch closure technique with an intact superior peroneal retinaculum (SPR). Methods From 2016 to 2020, 30 patients with recurrent dislocation of the peroneal tendon were treated with the current procedure. Clinical outcomes, including the time to resume running, the rate and time to return to sports, and the American Orthopaedic Foot and Ankle Society (AOFAS) Ankle-Hind Foot score, were evaluated preo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Consequently, we focused on the knotless suture bridge technique, frequently used in rotator cuff repair surgery [ 7 ], and the false-pouch closure technique [ 8 ] in peroneal tendon dislocation. This necessitated a fixation approach with a broader contact area, leading us to the knotless suture bridge technique.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, we focused on the knotless suture bridge technique, frequently used in rotator cuff repair surgery [ 7 ], and the false-pouch closure technique [ 8 ] in peroneal tendon dislocation. This necessitated a fixation approach with a broader contact area, leading us to the knotless suture bridge technique.…”
Section: Discussionmentioning
confidence: 99%
“…Adachi et al classified the bone morphology of the first centimetre proximal to the tip of the fibula into three categories (convex, flat, and concave), and compared 39 ankles with and without peroneal tendon dislocation; however, there was no significant difference in shape distribution between the two groups [2]. Nishimura and colleagues also compared the fibular morphology in 30 patients with dislocation with that in 30 controls using the same three categories and found no difference between the two groups [14]. Combined with the results of this study, these previous studies highlight the difficulty of identifying predisposing bone morphology using a classification based on the subjective qualification of distal fibular shape as convex, concave or flat.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the relationship between bone morphology and postoperative redislocation rate was investigated. A study by Kumai et al using 10 cadaver healthy ankles reported that the SPR played a major role in stabilizing the peroneal tendon [14]. In a recent systematic review of 14 studies, the postoperative dislocation rate was 1.1% (one in 90 patients) in the SPR repair group and 1.5% (two in 135 patients) in the combined groove deepening group, with low rates of redislocation using both techniques; however, no statistical analysis was conducted [25].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations